Spicer and Pegler's book-keeping and accounts - Bigg, Walter W.; Perrins, R.E.G. (London : H. F. L.; The English Language Book Society, 1971)
The principle of double entry book-keeping are described and illustrated full in Spicer and Pegler's practical book keeping and commercial knowledge and are only outlined in this book, which is devoted mainly to more advanced accountancy.
Including index.
osa 21/01/2019
Loans
Keywords: Accounting